Law Enforcement Against Criminal Acts of Drug Abuse Committed by Children - Ryan Fadli Siregar; Yasmirah Mandasari Saragih; Fauzan Fauzan; Putriani Nduru; Ibrahim Ibrahim (International Journal of Law and Society, 2025)
Children are the future generation of the nation that must be protected, especially when dealing with the law. Law enforcement against perpetrators of drug abuse crimes committed by children has been effective. Drug abuse has a very bad impact on the continuity of a nation's generation. To anticipate this, cooperation is needed from all components of society, such as families, from school to university level, and the government must unite in efforts to prevent narcotics in the surrounding environment. Using the perspective of Law Number 35 of 2009, this study attempts to analyze how narcotics crimes committed by children are prosecuted legally. Drug abuse is a serious crime that can endanger the security and sovereignty of the state, as well as the growth and future of the state, according to a normative legal approach that includes analysis of laws and regulations and previous events. Illegal drug use is prohibited, according to Law Number 35 of 2009. Research findings show that, despite the need for legal action against children who use drugs, the juvenile criminal justice system uses Restorative Justice strategies along with the concept of diversion to protect children from stigma.